Upstairs for Hebrew, Downstairs for English: The Jewish Community of Ste-Sophie, Quebec and Strategies for Public Education, 1914-1952 - MacLeod, Roderick; Poutanen, Mary Anne (Canadian Jewish Studies / Études juives canadiennes, 2002)
In general, Jews were outsiders with regard to Quebec’s publicschool system until the 1960s. Few were hired as teachersbefore the mid-twentieth century, and they could not be elected toschool boards. For some years at the beginning of the century,even the very right to schooling was in question for Jewish children.An exception to this outsider status was the ruralcommunity of Ste-Sophie. There Jews, who comprised themajority of the non-Catholic residents, succeeded in formingthe separate (“Protestant”) school board which maintained justone two-room school that catered to the special needs of Jewishchildren. The board also looked after other aspects of Jewish life in the community. This paper outlines the history of theschool and analyzes the developments that led to its establishment.